Association Between Reduced Daily Steps and Sarcopenic Obesity in Treatment-Seeking Adults With Obesity - Kreidieh, Dima; Itani, Leila; El Masri, Dana; Tannir, Hana; El Ghoch, Marwan (Frontiers in Endocrinology, 2020)
Objectives: Understanding the condition that describes the coexistence of obesity and sarcopenia, termed sarcopenic obesity (SO), is becoming a scientific and clinical priority. In this study, we aimed to assess the prevalence of SO in treatment-seeking adults with obesity and investigate any potential association between SO and a sedentary lifestyle, expressed in terms of daily steps. Methods: In this cross-sectional, prospective observational study, body composition and daily steps measurements were obtained using a segmental body composition analyser (Tanita BC-418) and an Omron HJ-320 pedometer, respectively, in 111 adults of both genders with obesity (body mass index; BMI ≥30 kg/m2), referred to the Outpatient Clinic in the Department of Nutrition and Dietetics at Beirut Arab University (BAU) in Lebanon. The participants were then categorized according to the presence of absence of SO, defined as an appendicular lean mass divided by body weight (ALM/weight) x 100%) of less than 23.40 and 29.60 in females and males, respectively. Results: Fifty-five of the 111 participants with obesity, with a mean age of 39.62±16.55 years and a mean BMI of 38.05±5.33 kg/m2 met the criteria for SO and displayed a significantly higher prevalence of inactivity (< 5,000 daily steps), i.e., nearly double (54.5% vs. 32.1%; p = 0.017) and they had a lower mean number of daily steps than those in the group without SO (5279 ± 2641 vs. 6732± 2989; p = 0.008). Linear regression analysis showed that SO is associated with a lower number of daily steps by 1,421 (β = -1421.4; -2508.9, -333.9; p=0.011) after adjusting for age, gender employment and the presence of cardiometabolic disease. Conclusion: Sarcopenic obesity affects nearly 50% of treatment-seeking adults with obesity. Moreover, it seems to be associated with a lower number of daily steps and a sedentary lifestyle. Future studies are needed to clarify whether this may influence clinical outcomes. If this is shown to be the case, weight management programmes should incorporate additional physical activity strategies in this population.